Online social networking an exploratory case study of the participation purposes of Filipino users - Que, Charmaine R.
This paper explored the participation purposes in online social networking of Filipino young adults, age 20-27, from the period of March to April 2004. This was an exploratory case study conducted among thirty Friendster® users. Data was collected using the information provided in the user profile and a researcher-made open-ended questionnaire. Results showed that 87 percent of the respondents joined the network by invitation. A large majority used the network for the primary purpose of connecting and meeting with friends, whether old, current or new ones. Only 10 percent used the network for dating purposes. Forty seven percent considered themselves "addicted" to the network and 63 percent were also members of other social networks. The results revealed users who log on to the network were motivated by the experience of growing their personal network of friends rather than with the intention of forming intimate relationships. This study recommends that computer subjects in the secondary home economics curriculum should include issues on development of human relationships via online social networks.